Penatalaksanaan Terapi Latihan Pada Kasus Fraktur Column Femur Dextra Di Rumah Sakit Orthopedi Dr. Soeharso Surakarta Tahun 2015 - Pratama, Aan Happy, Agus Widodo, S.Fis., M.Fis (2015)
Fracture or broken is a situation that the structure of bone occur discontinuation partly or totallity, cause of fracture is pressure or punch hardly and directly accepted by the bone. The pressure is caused by the strength suddenly and excessive such as hitting, crushing, bending, twisting, or retraction. To know management manual therapy in the case of fracture column femur in order to reduce pain, reduce oedema, range of motion, and functional activity in the case of fracture column femur use manual therapy modality. After four times therapy, the obtained results for static pain is T1 : 2 to T4 : 0, motion pain T1 : 4 to T4 : 1, press pain T1 : 5 to T4 : 2, increasing range of motion T1 S: 0o-0o-45o to T4 S: 0o-0o-95o and T1 F : 0o-0o-30o, to T4 F: 0o-0o-30o. increasing muscle strenght flexor hip T1 : 3 to T4 : 4, ekstensor hip T1 : 3 to T4 : 4, flexor knee T1 : 3 to T4 : 4, ekstensor knee T1 : 3 to T4 : 4, indeks barthel T1 : independence for 25 rating, to T4 : indepedence for 595 rating. Manual therapy can reduce degree of pain, reduce oedema, increase range of motion and functional activity in the case of fracture column femur dextra.